Web-Based Catering Application With "Mix Menu" Feature - Handayani, Siskha; Fani, Maidel; Sahrul Nizan, Muhamad (MSJ : Majority Science Journal, 2024)
The rapid increase in information technology has provided benefits to society in various fields, including culinary businesses such as catering. One example is Aisyah Purple Kuliner Catering, which offers various foods such as tumpeng rice, market snack cakes and traditional snacks. However, until now, this catering business has not fully utilized information technology such as a catering marketplace, which can facilitate communication and transactions between buyers and catering entrepreneurs. Apart from that, the process of collecting data and recording orders is still done manually, which results in problems in reporting order data. Therefore, the solution offered is to use a website in the catering business, by building a web-based application that uses a marketplace concept and has a "Mix Menu" feature. This feature allows customers to choose the items they want to order themselves, which makes it more similar to the experience of eating at a restaurant or food stall. This application was developed using the waterfall model and has been tested. Test results using the black box test showed that all application functionalities were running according to their function.